2021
DOI: 10.1108/ecam-10-2020-0880
|View full text |Cite
|
Sign up to set email alerts
|

Metrics development and modelling the mixed reality and digital twin adoption in the context of Industry 4.0

Abstract: PurposeThis paper aims to examine the current technology acceptance model (TAM) in the field of mixed reality and digital twin (MRDT) and identify key factors affecting users' intentions to use MRDT. The factors are used as a set of key metrics for proposing a predictive model for virtual, augmented and mixed reality (MR) acceptance by users. This model is called the extended TAM for MRDT adoption in the architecture, engineering, construction and operations (AECO) industry.Design/methodology/approachAn interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 60 publications
0
24
0
1
Order By: Relevance
“…Humanity resides at the beginning of a fourth industrial revolution more commonly known as Industry 4.0 [83,84], an inevitable result of several key technological breakthroughs that have changed economic, social, and political development. Schwab [12] proposes that the drivers of these breakthroughs fall into three categories, namely: (i) digital; (ii) physical; and (iii) biological, and that the implications of these technologies will shape industrial workflows moving forward.…”
Section: Industry 40 Constructionmentioning
confidence: 99%
“…Humanity resides at the beginning of a fourth industrial revolution more commonly known as Industry 4.0 [83,84], an inevitable result of several key technological breakthroughs that have changed economic, social, and political development. Schwab [12] proposes that the drivers of these breakthroughs fall into three categories, namely: (i) digital; (ii) physical; and (iii) biological, and that the implications of these technologies will shape industrial workflows moving forward.…”
Section: Industry 40 Constructionmentioning
confidence: 99%
“…The study covers seven basic aspects: energy saving and utilization, water saving and utilization, material saving and utilization, site space saving and utilization, indoor environment quality, green construction management, and operation management. Sepasgozar et al [20] present a set of identified factors leading to the usage of mixed reality digital twin, and these factors have been used to develop a predictive model to evaluate virtual, augmented, and mixed reality (MR) acceptance by users. Quantity indicators such as path coefficients, factor ranking, Cronbach's alpha, and chi-square test are used in this study.…”
Section: Existing Scoring Methodsmentioning
confidence: 99%
“…Sepasgozar et al. , 2020; Sepasgozar et al. , 2021) is expensive, and given that the building is now built, little can be done at this stage to effect meaningful change (Low Carbon Living, 2018).…”
Section: How Accurate Are Rating Tools At Assessment the Sustainability Of A Buildingmentioning
confidence: 99%